Development of precise protocol in the management of frozen shoulder : fusion of the myofascial pain assessment and conventional orthopaedic approaches - Abdul Jalil, Nizar; Mohamed, Abdul Hadi; Wan Ahmad, Wan Rohadiah (2009)
The term “frozen shoulder” is often under-diagnosed and hence undertreated. Traditional medical training and management of musculoskeletal pain have focused much attention on bones, joints and nerves. We introduce a new assessment tool of the frozen shoulder, integrating the conventional orthopaedic approaches with myofascial pain syndrome concept. We found that this approach is more precise and objective toward identifying the sources and pain diagnosis at the peri-articular shoulder joint area. By knowing the accurate diagnosis, more objectives treatment can be employed because shoulder pain often present with complex and multiple disorder at the same time. This approach comprises three most important assessment including shoulder impingement syndrome, myofascial pain syndrome and tendinitis/tear. We successfully managed six cases using this approach in identifying the underlying causes/ diagnosis for the ‘frozen shoulder’ and managed accordingly. We conclude that the key success of the ‘frozen shoulder’ management depends on the ability to identify the accurate diagnosis that made up this disorder.